2020
DOI: 10.22159/ijap.2020.v12s1.ff057
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Analysis of Pharmacokinetic Parameters of Several Oral Systemic Drugs Using Insilico Method

Abstract: Objective: This research aims to observe the pharmacokinetic parameters that can be predicted using a software, discover the best software to predictpharmacokinetic properties, and analyze the correlation between pharmacokinetic parameters used as descriptors with absorption percentage(%ABS) from references.Methods: This research was conducted using Molinspiration, QikProp, admetSAR, SwissADME, Chemicalize, and pkCSM software. This researchanalyzed 34 oral systemic drug compounds for absorption rate and six de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This is because modeling PK data means looking back at the data and extracting PK parameters. In contrast, simulation helps to predict what might happen in similar cases of the drug in question, looking at future circumstances [18]. There are several modeling strategies [2,3,9].…”
Section: Fig 1: Major Divisions Of Pkmentioning
confidence: 99%
“…This is because modeling PK data means looking back at the data and extracting PK parameters. In contrast, simulation helps to predict what might happen in similar cases of the drug in question, looking at future circumstances [18]. There are several modeling strategies [2,3,9].…”
Section: Fig 1: Major Divisions Of Pkmentioning
confidence: 99%
“…Swandana et al [23] showed that the pharmacokinetic parameters could be predicted using the in silico method.…”
Section: Introductionmentioning
confidence: 99%